Culture of primary ciliary dyskinesia epithelial cells at air-liquid interface can alter ciliary phenotype but remains a robust and informative diagnostic aid. - Robert A Hirst; Claire L Jackson; Janice L Coles; Gwyneth Williams; Andrew Rutman; Patricia M Goggin; Elizabeth C Adam; Anthony Page; Hazel J Evans; Peter M Lackie; Christopher O'Callaghan; Jane S Lucas (PLoS ONE)
Background The diagnosis of primary ciliary dyskinesia (PCD) requires the analysis of ciliary function and ultrastructure. Diagnosis can be complicated by secondary effects on cilia such as damage during sampling, local inflammation or recent infection. To differentiate primary from secondary abnormalities, re-analysis of cilia following culture and re-differentiation of epithelial cells at an air-liquid interface (ALI) aids the diagnosis of PCD. However changes in ciliary beat pattern of cilia following epithelial cell culture has previously been described, which has brought the robustness of this method into question. This is the first systematic study to evaluate ALI culture as an aid to diagnosis of PCD in the light of these concerns. Methods We retrospectively studied changes associated with ALI-culture in 158 subjects referred for diagnostic testing at two PCD centres. Ciliated nasal epithelium (PCD n = 54; non-PCD n  111) was analysed by high-speed digital video microscopy and transmission electron microscopy before and after culture. Results Ciliary function was abnormal before and after culture in all subjects with PCD; 21 PCD subjects had a combination of static and uncoordinated twitching cilia, which became completely static following culture, a further 9 demonstrated a decreased ciliary beat frequency after culture. In subjects without PCD, secondary ciliary dyskinesia was reduced. Conclusions The change to ciliary phenotype in PCD samples following cell culture does not affect the diagnosis, and in certain cases can assist the ability to identify PCD cilia.